Phase-dependent closed-loop deep brain stimulation of the fornix provides bidirectional manipulation of hippocampal theta oscillations - Isaac Grennan; Brook Perry; Anna Verghese; Melissa Jones; Oliver Härmson; Colin G. McNamara; Andrew Sharott (Brain Stimulation)
Introduction: Alzheimer's disease (AD) has very limited treatment options and therapies to prevent or reverse neurodegeneration remain elusive. Deep brain stimulation (DBS), whereby high-frequency pulses of electricity are delivered continuously to a specific part of the brain, has been trialled as an experimental treatment for AD. In AD patients, continuous, high frequency DBS targeted to the fornix (fx-DBS) has been shown to be safe, but not reliably effective across patients. In movement disorders, high-frequency DBS is thought to act as a virtual lesion, disrupting pathophysiological activity. In AD, it may be more advantageous to use stimulation to reinforce or rebuild oscillatory activities that are disrupted by the disease process. A primary candidate for such a target is the hippocampal theta oscillation, which provides a temporal framework for mnemonic processing and is altered in rodent models of AD. Material and methods: We applied closed-loop electrical stimulation to the fornix of rats traversing a linear track, triggered by different phases of the ongoing theta oscillation in the hippocampal local field potential (LFP) using the OscillTrack algorithm. Results: Stimulation at different target phases could robustly suppress or amplify the theta oscillation, and these effects were significantly larger than those caused by open-loop replay of the same stimulation pattern. Amplification of the theta oscillation could be achieved irrespective of the locomotor speed of the animal, showing that it did not result from a secondary effect of behavioural change. Conclusions: Our findings demonstrate that closed-loop fx-DBS is a viable method of modulating the amplitude of hippocampal theta oscillations that could be applied in human devices to provide a constructive intervention with the potential to boost memory circuit function in AD.